Obremenjenost svojcev, ki za bolnike po možganski kapi skrbijo doma - Čanč, Tanja (Rehabilitacija (Ljubljana), 2020)
Background: Caregiving for stroke survivors at home is demanding because of the complex consequences of stroke. In addition to numerous social roles, the family member as a caregiver acquires a new role, which can adversely affect his physical and mental health. The purpose of our study was to evaluate the burden of care of relatives caring for patients after stroke at home, and to estimate the correlation between the burden of care and the incidence of depressive symptoms in caregivers. Methods: The study included the caregivers of stroke patients who accomplished rehabilitation program at the University Rehabilitation Institute, Republic of Slovenia in 2016 and 2017. Caregivers' burden was assessed using the Zarit Burden Interview (ZBI) and eventual depressive symptoms using the Beck Depression Inventory (BDI II). Results: Sixty-two caregivers were included in the analysis. The average ZBI score was 31 points (range 2 to 69). The caregiver burden was moderately correlated with the functioning of the patient at discharge (Spearman rho = -0.43, p < 0.001), need for constant supervision (Spearman rho = 0.34, p = 0.006), receiving care allowance (Spearman rho = 0.37, p = 0.004), and higher incidence of depressive symptoms in caregiver Conclusions: Special attention should be given to family members who become caregivers when the patients are discharged home. In subacute stroke rehabilitation programs screening testing with ZBI should be performed as well as additional education and psychological support for those with a total ZBI score above 24.
Keywords: burden; caregivers; depresija; depression; Interviews as Topic; možganska kap; obremenjenost; rehabilitation; Stroke; svojci; Zarit Burden Interview; Zaritov vprašalnik obremenjenosti skrbnikov; ZBI